Migraine with Prolonged Aura: Correlation of Clinical and EEG Features - A. O. Ogunyemi (Behavioural Neurology)
Migraine with prolonged aura has rarely been examined with regard to the sequence of the neurological symptoms and the associated EEG changes. This report describes five patients who underwent clinical assessment and EEG recordings during attacks of migraine with prolonged aura. CT scan of the brain was obtained in four of them. Follow-up EEG was also obtained. The aura symptoms either preceded the headache or were coincident with it. The aura symptoms evolved in a manner consistent with posterior-to-anterior dysfunction of the cerebral cortex. The EEG abnormalities were non-epileptiform and consisted of focal delta slow waves or theta slow waves. The EEG abnormalities showed good correlation with the patients' aura symptoms and resolved when the patients became symptom free. The posterior-to-anterior sequence of the aura symptoms is in accord with the findings during cerebral blood flow studies in patients having migraine with aura. Also the symptoms and EEG changes in our patients indicate dysfunction of the cerebral cortex, consistent with the notion that spreading cortical depression may be the underlying pathophysiological event in migraine with aura.